2018
DOI: 10.1177/1024907917752959
|View full text |Cite
|
Sign up to set email alerts
|

The association between abnormal vital sign groups and undesirable patient outcomes

Abstract: Introduction: To determine the association between both abnormal individual vital signs and abnormal vital sign groups in the emergency department, and undesirable patient outcomes: hospital admission, medical emergency team calls and death. Method: We undertook a prospective cohort study in a tertiary referral emergency department (February-May 2015). Vital signs were collected prospectively in the emergency department and undesirable outcomes from the medical records. The primary outcomes were undesirable ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…Variation in vital signs is common and evidence suggests that using groups or combinations of abnormal vital signs, together with clinician gestalt, is superior to one abnormal vital sign in isolation. 36 The single patient who was transferred to the medical department had an abnormal heart rate and diastolic blood pressure. Further research should aim to assess which abnormal vital signs or combinations of abnormal vital signs have clinical value to predict undesirable outcomes in MHCUs.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in vital signs is common and evidence suggests that using groups or combinations of abnormal vital signs, together with clinician gestalt, is superior to one abnormal vital sign in isolation. 36 The single patient who was transferred to the medical department had an abnormal heart rate and diastolic blood pressure. Further research should aim to assess which abnormal vital signs or combinations of abnormal vital signs have clinical value to predict undesirable outcomes in MHCUs.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study was done at the tertiary referral emergency department to emphasize the association between abnormal vital signs and poor clinical outcomes and it showed that abnormal vital signs were predictors of unfavorable outcomes. They concluded that these abnormalities can guide the management plan and communication with the patients and their relatives [ 9 ]. While another study failed to formulate any evidence and highlighted the importance of more well-controlled studies in order to answer the research questions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esses achados convergem para outra pesquisa que avaliou o conjunto de sinais vitais alterados e os desfechos dos pacientes em um serviço de emergência e observou que, na admissão, a maioria dos homens com idade igual ou superior a 60 anos tinha alteração da frequência cardíaca, respiratória e temperatura. 18 Ainda nesse estudo, os pacientes que foram a óbito apresentavam mais de dois sinais alterados durante a permanência na emergência. 18 Portanto, pesquisas reforçam a importância da vigilância rigorosa do conjunto de parâmetros fisiológicos em uma unidade de emergência.…”
Section: Introdução Introdução Introdução Introduçãounclassified
“…18 Ainda nesse estudo, os pacientes que foram a óbito apresentavam mais de dois sinais alterados durante a permanência na emergência. 18 Portanto, pesquisas reforçam a importância da vigilância rigorosa do conjunto de parâmetros fisiológicos em uma unidade de emergência. 6,15,[18][19] Por fim, a realização da coleta de dados em uma única instituição por meio da análise retrospectiva de prontuários é uma limitação do estudo e tal fato deve ser considerado na generalização dos resultados.…”
Section: Introdução Introdução Introdução Introduçãounclassified